Modified Septic Tank Treatment System. (2016) - Anil, Rrtu; Neera, Anand Lali
Abstract: Water pollution is a major global problem. One of the main causes of ground water contamination is the effluent from septic tanks. Treatment of domestic wastewater using conventional septic tank is found to be inefficient leading to increased soil and ground water contamination. It's very important to protect surface and ground water from contamination. So there is a need for improving conventional septic tank. The purpose of this study was to investigate the effect of a modified septic tank system for treating domestic wastewater. Modified septic tank system is a simple means of treating domestic wastewater using the treatment mechanisms such as anaerobic digestion and disinfection. The effect of vertical baffles coupled with an anaerobic reactor on septic tank system was analysed. The reactor selected for the study consists of copper modified zeolite as an adsorbent which will also act as filter media on which attached growth process takes place. The results showed that vertical baffled septic tank(VBST) coupled with zeolite filter shows a good treatment system. The results also showed that vertical baffled septic tank coupled with zeolite filter with disinfection shows a removal of 99.99% total coliforms, 99.57% of TSS, 46.83% Ammonia nitrogen, 31.08% of nitrate nitrogen, 48.39% of total kjeldahl nitrogen, 94.4% of BOD and 71.74% of Phosphates. This study focuses on an economical and efficient decentralized treatment method for treating domestic waste water.